Industrial Training Report: Perpustakaan Tunku Bainun Universiti Pendidikan Sultan Idris / Hawa Hassan - Hassan, Hawa (Faculty of Information Management, 2018)
This report is contents the activities and the organization background of Tuanku Bainun Library, UPSI. The duration for the industrial training sessions take five months start from I st August 2018 until 31 st December 2018. Firstly, all the practical students have divided into each department for one person. The time rotation is within one month for practical students to change to another unit. All of the tasks done is based on schedule provided by the officer. Generally, Tuanku Bainun Library has fi ve main departments and sixteen units under of it. Thus, through this report will kindly present about the background of the organization, department structure and function and also the whole activities and task that practical students have involved. Thus, bein g as a traine e student, ther e is a lot of knowledge and experie nce gained from this course.